2018
DOI: 10.1007/s10329-018-0673-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating expert knowledge and ecological niche models to estimate Mexican primates’ distribution

Abstract: Ecological niche modeling is used to estimate species distributions based on occurrence records and environmental variables, but it seldom includes explicit biotic or historical factors that are important in determining the distribution of species. Expert knowledge can provide additional valuable information regarding ecological or historical attributes of species, but the influence of integrating this information in the modeling process has been poorly explored. Here, we integrated expert knowledge in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In general, results shown in Table 2 suggest that a direct use of GBIF records could be appropriate without an extensive exploration of other sources and a taxonomic expertise validation process in covering the realized environmental species niche requirements. Nevertheless, it could be highly dependent on the target taxonomic group, as for primates, the comparison of datasets without or with expert knowledge resulted in the recovering of a higher number of outliers in non-expert group 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, results shown in Table 2 suggest that a direct use of GBIF records could be appropriate without an extensive exploration of other sources and a taxonomic expertise validation process in covering the realized environmental species niche requirements. Nevertheless, it could be highly dependent on the target taxonomic group, as for primates, the comparison of datasets without or with expert knowledge resulted in the recovering of a higher number of outliers in non-expert group 97 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed biological knowledge is still scarce or incomplete for many if not most Amazonian plant species. Therefore, expert‐based information has been proposed as an alternative approach to identifying meaningful predictors in habitat modeling (Calixto‐Pérez et al, ). Our findings showed that PCA was effective in reducing omission error rates, data collinearity, and dimensionality, as well as preserving maximum variance, when applied to a set of variables preselected by experts.…”
Section: Discussionmentioning
confidence: 99%
“…The value and importance of a well‐constructed SDM have motivated an explosion of methods aimed at building more accurate models (Elith et al, ; Kuhnert, Martin, & Griffiths, ). However, few efforts have been made to develop a collaborative model‐building process among modelers, ecologists, and decision‐makers to improve model quality (Calixto‐Pérez et al, ) and to facilitate clear communication of model results (Addison et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that this species is most vulnerable to drought during the dry season, and that dry and warm conditions negatively affect seed production (Thomas et al, 2017 Detailed biological knowledge is still scarce or incomplete for many if not most Amazonian plant species. Therefore expert-based information has been proposed as an alternative approach to identifying meaningful predictors in habitat suitability modelling (Calixto-Pérez et al, 2018). Our findings showed that PCA was effective in reducing omission error rates, data collinearity and dimensionality, as well as preserving maximum variance, when applied to a set of variables pre-selected by experts, following Dormann et al (2013). recommendations.…”
Section: Amazon-nut Habitat Suitabilitymentioning
confidence: 68%
“…The value and importance of a well-constructed SDM has motivated an explosion of methods aimed at building more accurate models (Elith et al, 2011;Kuhnert, Martin, & Griffiths, 2010). However, few efforts have been made to develop a collaborative model-building process among modellers, ecologists, and decision-makers to improve model quality (Calixto-Pérez et al, 2018) and to facilitate clear communication of model results (Addison et al, 2013).…”
Section: Introductionmentioning
confidence: 99%